2013
DOI: 10.1111/efp.12085
|View full text |Cite
|
Sign up to set email alerts
|

Gene × environment tests discriminate the new EU2 evolutionary lineage of Phytophthora ramorum and indicate that it is adaptively different

Abstract: A new evolutionary lineage of the destructive introduced tree pathogen Phytophthora ramorum, EU2 lineage, was recently discovered attacking larch and other hosts in Northern Ireland and south west Scotland, UK. Sixteen 'medium 9 agar concentration 9 incubation temperature' stress environments were tested to find a rapid and repeatable method to discriminate the known EU2 lineage from the EU1, NA1 and NA2 lineages in culture, in particular from the EU1 already prevalent across the UK; and to investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Previous studies reported the EU2 lineage from Japanese larch, bilberry, rhododendron and non‐native red oak (Van Poucke et al ., ; Franceschini et al ., ). The present study has provided the first confirmed findings of natural infection by EU2 on European larch, hybrid larch, beech, noble fir and western hemlock.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies reported the EU2 lineage from Japanese larch, bilberry, rhododendron and non‐native red oak (Van Poucke et al ., ; Franceschini et al ., ). The present study has provided the first confirmed findings of natural infection by EU2 on European larch, hybrid larch, beech, noble fir and western hemlock.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, the distribution of the EU2 lineage is similar to that reported previously, and there is no evidence of rapid invasive spread into other parts of Scotland or expansion into either England or Wales. However, EU2 is more widespread in southwest Scotland than previously reported (Van Poucke et al ., ; Franceschini et al ., ) and its range now includes more southern and eastern parts of the Dumfries and Galloway region. In 2013 heavy larch mortality occurred in this part of southwest Scotland, with around 4000–6000 ha of larch (out of 8000–9000 ha in total) estimated to be affected following aerial surveys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that "nothing in forest pathology makes sense except in the light of evolution," paraphrasing Dobzhansky, could now seem obvious and not deserving of further development (Varki 2012). Many recent articles dealing with forest pathology indeed have an evolutionary background (e.g., Hansen and Goheen 2000;Pinon and Frey 2005;Kinloch et al 2008;Garbelotto et al 2010;Hayden et al 2011;Cruikshank and Jaquish 2014;Franceschini et al 2014). However, we contend that an evolutionary perspective is still not sufficiently emphasized and applied to the management of forest diseases.…”
mentioning
confidence: 99%